2004
DOI: 10.1159/000077119
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study between AudiovisualSexual Stimulation Test and Nocturnal Penile Tumescence Test Using RigiScan Plus in the Evaluatio n of Erectile Dysfunction

Abstract: Introduction: Although the nocturnal penile tumescence (NPT) test is considered the gold standard for the differential diagnosis of psychogenic versus organic erectile dysfunction (ED), concerns have recently been raised regarding the financial and time expenditure it demands. We evaluated the diagnostic efficacy of the audiovisual sexual stimulation (AVSS) test as an alternative to the NPT test. Patients and Methods: A total of 43 patients with ED were examined. Each patient filled in an International Index o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…Although an obvious limitation of the technique derives from the fact that it cannot provide a continuous monitoring of time-related events, the DIR has recently come to be used broadly in the field of ED [10,11] . It is a very fast technique with no pain, and can be used by the patient himself at home and also in the consulting room after injection of vasodilating drugs or/and audiovisual sexual stimulation [12] . Overall, the results of the present study revealed a good correlation between axial penile rigidity and radial penile rigidity.…”
Section: Discussionmentioning
confidence: 99%
“…Although an obvious limitation of the technique derives from the fact that it cannot provide a continuous monitoring of time-related events, the DIR has recently come to be used broadly in the field of ED [10,11] . It is a very fast technique with no pain, and can be used by the patient himself at home and also in the consulting room after injection of vasodilating drugs or/and audiovisual sexual stimulation [12] . Overall, the results of the present study revealed a good correlation between axial penile rigidity and radial penile rigidity.…”
Section: Discussionmentioning
confidence: 99%
“…26 An NPTR outline with at least an erectile episode characterized by 60% rigidity at both base and tip for at least 10 min is considered to be normal. 27 Total lack of rigidity at 60-79% at altitudes higher than 4450 m in individuals that are healthy and strong at sea level shows the key role played by chronic hypoxia in the reduction of erythrocyte sedimentation rates.…”
Section: Discussionmentioning
confidence: 99%
“…[1] The other diagnostic methods, which are more invasive than NPT test, are color Doppler sonography, dynamic cavernosometry, and cavernosography. Three methods can be used for the assessment of erectile capacity: measurement of spontaneous erections during night sleep, the erectile response to AVSS in laboratory, and measurement of the response to intracavernosal smooth muscle relax-ants such as prostaglandin E1.…”
Section: Discussionmentioning
confidence: 99%
“…Three methods can be used for the assessment of erectile capacity: measurement of spontaneous erections during night sleep, the erectile response to AVSS in laboratory, and measurement of the response to intracavernosal smooth muscle relax-ants such as prostaglandin E1. [1] We aimed to investigate the role of AVSS test in differentiation of psychogenic and organic ED. Of the three methods, NPT measurement is the first objective diagnostic approach to differentiate psychogenic and organic ED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation